Parenthood, Alcohol Intake, and Drinking Contexts: Occasio Furem Facit - Paradis, Catherine (Rutgers University, 2011)
OBJECTIVE: The aim of this study was to assess whether the effect of parenthood on alcohol intake varies according to the context in which the drinking act occurs. METHOD: The data were drawn from the Canadian Addiction Survey, a national telephone survey conducted in 2004. The analytical sample included 1,079 drinking occasions nested in 498 female drinkers and 926 drinking occasions nested in 403 male drinkers between 18 and 55 years of age. A multilevel linear statistical model was used to estimate the variance related to the drinking occasion (Level 1) and to the parental role (Level 2). RESULTS: Parenthood was not associated with alcohol intake per occasion. Drinking context variables brought great explanatory power to the study of alcohol intake, but, overall, the effect of parenthood on alcohol intake did not vary according to the context in which drinking occurs. Only one interaction between the parental role and contextual characteristics was found. CONCLUSIONS: Men's and women's alcohol intake within drinking contexts is more likely to be influenced by the immediate context in which drinking occurs than by their parental role. The explanation for alcohol behaviors within the general Canadian population may lie as much in the situation as in the person.